2010
DOI: 10.1007/s12094-010-0585-6
|View full text |Cite
|
Sign up to set email alerts
|

SEOM clinical guidelines for the treatment of metastatic breast cancer

Abstract: Patients with metastatic breast cancer have a wide number of treatment options, including medical, surgical, and supportive care measures. Treatment decisions are based in predictive and prognostic factors and the informed choice of the patients. SEOM has elaborated these guidelines with evidence-based recommendations for the diagnostic work-up, treatment (chemotherapy, endocrine therapy and targeted therapies) and supportive care for the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The review of national guidance (either clinical guidelines or HTA reports) identified five documents on breast cancer care for England and Wales ( 49 – 53 ), three from Spain ( 54 – 56 ), and six from Sweden ( 57 – 62 ). The Cancer Strategy document published by the Spanish Ministry of Health ( 54 ) makes no treatment-specific recommendations, so we also reviewed the two Spanish Society of Medical Oncology (SEOM) guidelines ( 55 ; 56 ) although these are not “official” guidance. In all countries, guidelines covered the whole disease pathway incorporating early, advanced, and metastatic disease.…”
Section: Resultsmentioning
confidence: 99%
“…The review of national guidance (either clinical guidelines or HTA reports) identified five documents on breast cancer care for England and Wales ( 49 – 53 ), three from Spain ( 54 – 56 ), and six from Sweden ( 57 – 62 ). The Cancer Strategy document published by the Spanish Ministry of Health ( 54 ) makes no treatment-specific recommendations, so we also reviewed the two Spanish Society of Medical Oncology (SEOM) guidelines ( 55 ; 56 ) although these are not “official” guidance. In all countries, guidelines covered the whole disease pathway incorporating early, advanced, and metastatic disease.…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical guidelines are available for MBC 3–9 , but recommendations and optimal treatment sequences are still not clearly standardized 10 , and there is a pressing need for optimal and homogeneous treatment sequences. MBC treatment is an evolving field in which new drugs and therapies are emerging, and therefore oncologists usually combine solid evidence from clinical trials with their personal experience when choosing the best therapy.…”
Section: Introductionmentioning
confidence: 99%